BTLA-HVEM Couple in Health and Diseases: Insights for Immunotherapy in Lung Cancer - Demerlé, Clemence; Gorvel, Laurent; Olive, Daniel (Frontiers in Oncology, 2021)
Lung cancers are the leading cause of cancer deaths worldwide. Immunotherapies (IT) have been rapidly approved for lung cancer treatment after spectacular results in melanoma. Responses to currently used checkpoint inhibitors are strikingly good especially in metastatic diseases. However, durable responses are observed in only 25% of cases. Consequently, there is an urgent need for new immunotherapy targets. Among the multiple checkpoints involved in the tumor immune escape, the BTLA-HVEM couple appears to be a promising target. BTLA (B- and T- Lymphocyte Attenuator) is a co-inhibitory receptor mainly expressed by B and T cells, repressing the activation signal transduction. BTLA shares similarities with other immune checkpoints such as PD-1 and CTLA-4 which are the targets of currently used immunotherapies. Furthermore, BTLA expression points out terminally exhausted and dysfunctional lymphocytes, and correlates with lung cancer progression. BTLA’s ligand is HVEM (Herpes Virus Entry Mediator) which belongs to the TNF receptor family. Often described as a molecular switch, HVEM is constitutively expressed by many cells, including cells from tumor and healthy tissues. In addition, HVEM seems to be involved in tumor immuno-evasion, especially in lung tumors lacking PD-L1 expression. Here, we propose to review the role of BTLA-HVEM in immuno-escape in order to highlight its potential for designing new immunotherapies.